GONDANG SABANGUNAN DAN MANGALAP TONDI : RITUAL WARISAN BUDAYA BATAK YANG DIPERCAYA MEMBERIKAN KESEMBUHAN - Donda Purba (Jurnal Medika Hutama, 2026)
Background : ‘Mangalap tondi’ is a traditional healing practice of Batak Toba tribe accompanied by ‘gondang sabangunan’ rooted in spiritual beliefs. Objective : Explores the healing ritual through neurological and psychiatric perspectives, especially the relation between subconcious and hypnotherapy . Methods : Literature review using sources from neurology, psychiatry and culture. Results : Therapeutic effects generated by ritual ‘mangalap tondi’ through rythmic auditory stimulation and also culturally beliefs. ‘Gondang sabangunan’ can induce relaxation and altered states of conciousness similar to hypnosis and can be alligned with psycoanalytic concepts of subconciuosness and the principle of hypnotherapy, focused on attention and suggetibility in managing mental and physical conditions. Conclusions : The ritual reflects culturally embedded healing practice aligned to hypnotherapy and neuropsychological approachment. By integrating multidisciplinary may support mental health care approachment to culturally sensitive society